Edukasi Mitigasi Bencana dalam Upaya Peningkatan Kesiapsiagaan di Posyandu Remaja Puskesmas Mabelopura Kota Palu - Muhammad Rizki Ashari; Nur Mila Sari; Vidiyanto Vidiyanto; Novi Inriyanny Suwendro; Miftahul Haerati; Mohammad Ilham; Gilang Pradana Perkasa Bahmid (Bahasa Indonesia, 2026)
Adolescents in Palu City live in a seismic and tsunami-prone area, while initial coordination with the Youth Posyandu of Mabelopura Community Health Center indicated that structured disaster-mitigation education had not been provided routinely. This community service activity aimed to strengthen the cognitive component of disaster preparedness among adolescents through disaster-mitigation education integrated into Youth Posyandu activities. The activity was conducted on 13 September 2025 at the Lembaga Dakwah Islam Indonesia (LDII) Islamic Boarding School in Palu City and involved 50 adolescent participants. The implementation consisted of coordination with the community health center, a 10-item pre-test mapped to cognitive preparedness indicators, a 45-minute interactive education session using PowerPoint and earthquake-mitigation leaflets, discussion, and a post-test. The evaluation measured changes in disaster-mitigation knowledge; practical evacuation skills were identified as an aspect requiring follow-up simulation. The mean percentage of correct answers increased from 72.0% before education to 88.2% after education, with improvement in 8 of 10 indicators. The largest improvement occurred in the structural and non-structural mitigation indicator (from 6% to 60%; +54 percentage points), followed by the basic concept of mitigation (+40 percentage points) and the purpose of mitigation (+36 percentage points). The activity improved adolescents' knowledge and awareness of actions before, during, and after earthquake/tsunami events and supports Youth Posyandu as a community-based channel for disaster education. Future programs should combine education with evacuation drills and observational checklists to assess skills-based preparedness.